Media Komunikasi Pemasaran Usaha Jamu Buk Tum Didesa Andongsari Kecamatan Ambulu - Rizqi, Lika (Medio Jurnal Ilmu Komunikasi, 2023)
Technological civilization is developing very quickly with many advances in the economic, political, socio-cultural and educational fields. In the field of marketing, communication is very much needed to market products and services. Current technological capabilities answer all challenges on how to market products and services more effectively and efficiently. Increasingly developing technology makes communication possible using communication media. Communication is carried out using communication media, namely WhatsApp. Whatsapp is a cross-platform messaging application that allows us to exchange voice and text messages without using credit, because WhatsApp uses the internet or wifi network. The title of this research is "Using Whatsapp as a Marketing Communication Media for the Buk Tum Herbal Medicine Business in Andongsari Village, Ambulu District." From this title, WhatsApp social media can be used to carry out communication interactions between sellers and potential buyers. This research method uses descriptive qualitative research methods where data is collected through observations carried out in the field, interviews conducted in the field and documentation carried out in the field. The use of digital marketing communications is carried out to exchange information between participants and communicators via WhatsApp social media.